Earplug - Soo Jing Yuan, Soo Jing Yuan; Foo, Shu Khai; Othman, Siti Amira (Penerbit UTHM, 2020)
Earplug have been created since a long time ago, the earliest patent earplug was made in 1884. Human tend to use finger to cover their ears to blocking the noise absorb by the ear. It was surprisingly effective but human unable to sustain for a long period of time and while using finger to decrease the volume, human unable to do other work in such condition.